A Technical Study on the Effect of Hydrothermal and Dry Heat Shrinkage of Different Shoe-Upper Leathers Used in Pakistan - Solangi, Barkat Ali; Zehra, Beena; Nawaz, Hafiz Rub; Nadeem, Uzma; Pervez, Mohammad Kashif; Zeeshan, Mohammad (Indonesian Scholar Society, 2023)
The shrinkage of leather becomes a problem when leather is used in the form of leather shoes or other products and is heated at a high temperature. This technical study addressed shrinkage occurring in most leather shoes used in Pakistan during the shoe manufacturing process. The chemical testing results revealed fat content (4.0-4.5%), chromic oxide (2.3-2.5%), ash content (1.3-1.6%), and pH (3.5-3.7) under significant limits. The effects of hydrothermal and dry heat shrinkage were investigated in selected shoe-upper leathers. The leather samples showed (18-41%) shrinkage in all 03 samples. The results revealed that an extensive change in various physical tests, such as tensile strength, % elongation, tear strength, had been found with heat induction. The temperature and time of heat contact significantly affect the destruction of bonding in shoe upper leather after being converted into shoes.